Ensuring Individual Rights through Institutional Freedoms: The Role of Religious Institutions in Securing Religious Rights - Fox, Jonathan (Religions, 2021)
Understanding the restrictions placed on religious institutions and associations, or the freedoms that they are denied, is essential for understanding the limits placed on individual religious freedoms and human rights more generally. This study uses the Religion and State round 3 (RAS3) dataset to track restrictions faced by religious organizations and individuals between 1990 and 2014 and explores how reduced institutional freedoms results in fewer individual freedoms. We find that restrictions on both institutional and individual religious freedoms are common and rising. Restrictions on institutional religious freedom are harsher against religious minorities than restrictions on individual freedoms. However, against the majority religion, restrictions on individual religious freedoms are harsher.